La interdisciplinaridad en los procesos de planificación por proyectos orientados a generar aprendizajes significativos - Luna Benavides, Enma Estela (2022)
Interdisciplinarity is the relationship that is established between one science with others in order to provide connections and generate projective knowledge, in its exercise, the educator is a motivating person and committed to his profession, fosters in students skills to solve problems and especially generate significant learning, hence its importance and incorporation into the educational process. In this context, the present investigation called "Interdisciplinarity in the planning processes by projects aimed at generating significant learning" aims to generate a methodological proposal for the planning of interdisciplinary classroom projects in the middle sublevel in the second bimester in the period 2021-2022 of the ¨Padre Julían Lorente¨ Educational Unit, a proposal that was born with the intention of contributing to the training of teachers in interdisciplinary projects. The methods used for the development of this research were inductive, deductive, inductive-deductive, analytical, synthetic, hypothetical-deductive, the same ones that helped me to organize, process and analyze the information. The study is descriptive and not experimental, for this reason the planning of 6 interdisciplinary educational projects of the middle level of basic general education has been reviewed. It is concluded that when applying interdisciplinarity in project planning there are confusions regarding its adaptation and it ends up working in a disciplinary way. Keywords: interdisciplinarity, Learning, Planning, Teaching, Discipline. .